PROGRAM PENANGGULANGAN KECELAKAAN LALULINTAS DI PERLINTASAN KERETA API SEBIDANG DI WILAYAH JAWA TENGAH - Lambang Antono (Universitas Jenderal Ahmad Yani, 2023)
One of the transportation problems still faced in the country is the problem of traffic accidents that not only occur on roads and highway intersections, but also those that occur at level crossings between trains and motorized vehicles. Such as the train accident in Silebu Village, Kragilan District, Serang Regency, Banten Province on July 26, 2022 which killed 9 people. In the end, the issue of railroad crossings is not enough to be seen from one aspect of the problem alone but extends to other fields because it involves the various roles of actors, signals/codes, field space, and the morality of the users themselves. The number of railway crossings on the Central Java Regency / City road according to data from the Directorate General of Railways of the Ministry of Transportation in 2022 was recorded at 834 level crossings spread across 23 districts / cities, with details of 476 unguarded crossings and 268 guarded crossings. Starting from this condition, this research was conducted as a premise for Research on Safety Countermeasures Program at Railway Crossings in Central Java, especially both level crossings on provincial roads and on Regency / City roads.